Trends and risk of lung cancer among people living with HIV in the USA: a population-based registry linkage study. Issue 10 (October 2022) - Haas, Cameron B; Engels, Eric A; Horner, Marie-Josèphe; Freedman, Neal D; Luo, Qianlai; Gershman, Susan; Qiao, Baozhen; Pfeiffer, Ruth M; Shiels, Meredith S
Summary: Background: Lung cancer is a common cancer in people living with HIV, but the risk of cancer in this group has not been investigated for over a decade. We investigated trends in relative and absolute risk of lung cancer among people living with HIV of various age groups in the USA. Methods: In this population-based registry linkage study, we used 2001–16 data from the HIV/AIDS Cancer Match study, which links data from HIV and cancer registries from 13 regions in the USA. We included non-Hispanic White, non-Hispanic Black, and Hispanic individuals living with HIV aged 20–89 years in our study population. Average annual percentage changes in lung cancer rates were estimated with multivariable Poisson regression, and standardised incidence ratios (SIRs) and excess absolute risks were estimated comparing people living with HIV with the general US population. We used non-parametric cumulative incidence curves to estimate the 5-year cumulative incidence of lung cancer and two AIDS-defining cancers (non-Hodgkin lymphoma and Kaposi sarcoma). Findings: There were 3426 lung cancers in 4 310 304 person-years of follow-up in our study population. Age-standardised lung cancer incidence rates in people living with HIV declined by 6% per year (95% CI –7 to –5) during 2001–16, with greater declines in the 20–29 age group (–11%, –16 to 6) than in the older age groups (eg, –3% [–6 to 1] in those aged 70–89 years). During 2013–16, the SIR of lung cancer in people living with HIV was 2·01 (95% CI 1·52 to 2·61) in those aged 40–49 years, and 1·31 (1·12 to 1·52) in those aged 60–69 years, whereas the excess absolute risk among people living with HIV was 11·87 (3·95 to 21·89) per 100 000 person-years for those aged 40–49 years and 48·23 (6·88 to 95·47) per 100 000 person-years for those aged 60–69 years. Beginning in 2011, the 5-year cumulative incidence for lung cancer (1·36%, 95% CI 1·17 to 1·53) surpassed that of Kaposi sarcoma (0·12%, 0·06 to 0·17) and non-Hodgkin lymphoma (0·45%, 0·35 to 0·56) for people living with HIV aged 60–69 years. Interpretation: Between 2001 and 2016, the risk of lung cancer decreased for people living with HIV aged 20–69 years, but remained substantially elevated compared with the general population, probably due to a combination of smoking and immunosuppression. For people living with HIV aged 60 years and older, the risk of lung cancer exceeds that of two of the most common AIDS-defining cancers, highlighting the importance of lung cancer among the growing older population of people living with HIV. Funding: Intramural Research Program of the US National Cancer Institute.